(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
In addition to study the genetic information of capsular polysaccharide gene by PCR assay .This study is also, aimed to determine the molecular serotyping among different environmental resources samples of Cryptococcus neoformans, by using phenotypic and molecular techniques. So, this study is designed to investigate the molecular serotyping of C. neoformans at a genetic level in order to identify the serotypes belong to this yeast and to differentiate them from each other. To achieve these goals, environmental resources samples were collected from different area of Najaf province during (2015). Culture tests are done for samples in The same aspect includes identification by molecular methods. The polymerase chain reaction method (PCR) is used to identify the Cryptococcus serotype genetically. Depending on amplification of genomic DNA, the entire isolates are diagnosed as Cryptococcus yeasts. However, the most recurring species are the C. neoformans that rated 80%, while the C. gattii that rated 20% is the less recurring one. The results of amplifing the genomic DNA, using specific primer, show bands with molecular weight that is (387 bp) approximately for 12 isolates. However, the other species showed band with molecular weight that was (359 bp). The isolates are diagnosed genetically using the RFLP – PCR method as restriction enzyme with (Bsm F1, Hpa II) through which systematic important information appears for the genetic relations in the studied isolates that are related for two types. PCR assay revealed that five different serotypic patterns are detected as: serotype A ,serotype B , serotype C , serotype D and serotype AD .It can be concluded that the PCR targeting the genomic DNA and the REFP – PCR are rapid and simple techniques for serotyping C. neoformans and are useful not only for discrimination of C. neoformans from its related species, but also for epidemiological study at the molecular level. This study provides the detection genetically serotyping of C. neoformans which is isolated from different environmental resources in Najaf province